If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (u + -6) * 10 = 100whatisu Reorder the terms: (-6 + u) * 10 = 100whatisu Reorder the terms for easier multiplication: 10(-6 + u) = 100whatisu (-6 * 10 + u * 10) = 100whatisu (-60 + 10u) = 100whatisu Solving -60 + 10u = 100ahistuw Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-100ahistuw' to each side of the equation. -60 + -100ahistuw + 10u = 100ahistuw + -100ahistuw Combine like terms: 100ahistuw + -100ahistuw = 0 -60 + -100ahistuw + 10u = 0 Add '60' to each side of the equation. -60 + -100ahistuw + 60 + 10u = 0 + 60 Reorder the terms: -60 + 60 + -100ahistuw + 10u = 0 + 60 Combine like terms: -60 + 60 = 0 0 + -100ahistuw + 10u = 0 + 60 -100ahistuw + 10u = 0 + 60 Combine like terms: 0 + 60 = 60 -100ahistuw + 10u = 60 Reorder the terms: -60 + -100ahistuw + 10u = 60 + -60 Combine like terms: 60 + -60 = 0 -60 + -100ahistuw + 10u = 0 Factor out the Greatest Common Factor (GCF), '10'. 10(-6 + -10ahistuw + u) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(-6 + -10ahistuw + u)' equal to zero and attempt to solve: Simplifying -6 + -10ahistuw + u = 0 Solving -6 + -10ahistuw + u = 0 Move all terms containing u to the left, all other terms to the right. Add '6' to each side of the equation. -6 + -10ahistuw + 6 + u = 0 + 6 Reorder the terms: -6 + 6 + -10ahistuw + u = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -10ahistuw + u = 0 + 6 -10ahistuw + u = 0 + 6 Combine like terms: 0 + 6 = 6 -10ahistuw + u = 6 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -4q-8=16 | | 5x^8+35x^7+60x^6= | | 10t-20=60 | | (8a-7b)=16a^2b-14ab^2 | | 10+-20=60 | | N-41=20+4 | | -4(c+1)+2c=3(2b-1) | | 4(4y+5)=60+5(y+3) | | x^5-x^4-5x^3-x^2+8x-4=0 | | 4(-5y+1)=-96 | | k.1/3=5 | | 6+8n+2+8n+2= | | 3N+5=40+25 | | X^2-5x+6=6x-18 | | 12b-5-2b=2 | | A(x+2)+B(x-1)-1=0 | | 3x-4+5=x | | 1.5=2/1.7 | | n^3-6*n^2+5*n-324=0 | | 4x+2=3-(5x-6) | | 2m^2-7m=12 | | 3x-4-5=x | | 7(x+1)=-14 | | 17-4x=13+x | | -7xb=b-49 | | X-.75X=25 | | x+2+7x=-16 | | x=(y+4)*log(2y+3) | | 3x^2-8x+3y^2+4=0 | | 216z^3-125y^3= | | B/19-7b/19=54/19 | | 4=x/5=3 |